Comparison of performance between a native app and a mobile web application for monitoring a photovoltaic system (2016)
A native Android application and a multi-platform web application to monitor solar radiation and the output power of a photovoltaic system were developed, in order to establish which is more efficient using the mobile device resources. The methodology for Mobile Application Development [MAD] was adopted and free software tools –Android Studio and HTML5– were used. CPU consumption, response time in sending data and memory usage for the execution of the appli-cations, were compared; also, the user experience was evaluated through the 6Ms survey. The transfer time of a data from the server to the mobile application executed in Chrome was 0.887 seconds, the native application transfers a data in 0.853 seconds –both times are within the acceptable ranges, since the acquisition system stores one data every 5 minutes; the ave-rage memory usage was 182 Mb for executing the application in the Chrome browser, while the native application achieved a reduction of 65%, therefore it can be concluded that the native application requires less memory usage for its execution.